Association of type D personality with vascular health in adolescents - Fangman, Cheng; Han, Lv; Nan, Sheng; Binqian, Ge; Ying, Liu; Chunmei, Zhang; Ping, Zhou; Fenfen, Zhu; Juan, Shen (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThis study aimed to evaluate the association between type D personality and vascular health in adolescents.MethodsA total of 645 adolescents were involved in this study. All completed questionnaires assessing demographic and sociological characteristics, Type D personality Scale, Scale for Healthy Lifestyle of College Students (SHLCS), and Self-Rating Scale of Sleep (SRSS). Vascular health was evaluated using a fingertip sensor with biofeedback technology to measure vascular wall elasticity. The effect of type D personality was analyzed using both dichotomous and continuous methods.ResultsWhen analyzed as a binary variable, type D personality significantly affected vascular health scores [β = −0.169, 95% confidence interval (CI): [−4.001 to −1.483], P < 0.001]. When treated as continuous variables, negative affectivity (NA) exhibited an independently negative association with vascular health [β = −0.240, 95% CI: (−0.569 to −0.049), P = 0.020], whereas social inhibition (SI) and the interaction between NA and SI did not demonstrate significant effects. Additionally, abdominal circumference [β = −0.171, 95% CI: (−0.198 to −0.039), P = 0.004], pulse rate [β = −0.093, 95% CI: (−0.127 to −0.010), P = 0.021], and SRSS score [β = −0.155, 95% CI: (−0.336 to −0.110), P < 0.001] were negatively associated with vascular health. Conversely, stress tolerance [β = 0.211, 95% CI: (0.062–0.139), P < 0.001], exercise behavior [β = 0.078, 95% CI: (0.001–0.192), P = 0.048], and stress management behavior [β = 0.226, 95% CI: (0.328–0.780), P < 0.001] were positively associated with better vascular health.ConclusionThe findings suggest that type D personality is associated with vascular health in adolescents. Moreover, the NA component of the type D, but not the SI and NA*SI interaction, may drive the connection between type D personality and vascular health in adolescents. These findings highlighted the importance of initiating cardiovascular and cerebrovascular health promotion and disease prevention strategies from childhood.